Shalmaneser III and the Levantine States: The “Damascus Coalition Rebellion” - A. Kirk Grayson (Journal of Hebrew Scriptures, 2005)
This article serves to promote the interaction between biblical scholars and archaeologists as well as other specialists in ancient Near Eastern Studies. It discusses the Western policy begun by Shalmaneser III and its impact in the Levant in general and Israel and Judah in particular. The Assyrians had great knowledge of, and interest in, foreign lands, their cultures, economies, and languages. It is hard to believe that they did not, with their disciplined structure and extensive knowledge of the world around them, have long-range plans to which the aims of the annual campaigns, barring emergencies, adhered.